Attachment Aware Schools: the impact of a targeted and collaborative intervention. (3rd April 2019) - Rose, J.; McGuire-Snieckus, R.; Gilbert, L.; McInnes, K.
ABSTRACT: The Attachment Aware Schools (AAS) project was a targeted and collaborative intervention between academics and school-based practitioners. The aim of the project was to promote practitioner awareness of attachment in relation to child behaviours and learning. It focused on using relational-based strategies and interventions to address the needs of children and young people. The AAS framework promoted Emotion Coaching as a universal, relational-based practice approach, with specialised targeted support for children with additional needs. Supportive managerial strategies and setting policies sustained the integration and maintenance of attachment-informed practice and school ethos. This article reports the findings from the project which included over 200 participants (107 teaching and support staff and 94 pupils aged 5 to 16 years), from 40 schools, in two different Local Authorities within the UK. Adopting a mixed methods approach, qualitative and quantitative data provided hard and soft indicators of improved pupil and adult outcomes. Findings demonstrated significant improvements in pupils' academic achievement in reading, writing and maths. There were significant decreases in sanctions, exclusions and overall difficulties. Practitioners reported a positive impact on professional practice, adult self-regulation and emotional self-control, and were more confident when talking with children about emotions. This project contributes to the growing evidence based on the effectiveness of whole school attachment-based strategies and is already demonstrating policy implications at a national level.